PENINGKATAN PENGETAHUAN AYAH SEBAGAI UPAYA PREVENTIF DAMPAK ASAP ROKOK TERHADAP IBU HAMIL DAN TUMBUH KEMBANG ANAK - Cici Monika Sari; Emi Sutrisminah; Dian Salsabila; Putri Nur Rahmawati; Putri Yuliana (WASATHON Jurnal Pengabdian Masyarakat, 2026)
Abstract The smoking habit of family members, especially fathers, can have a negative impact on the health of pregnant women and children, both directly and through exposure to secondhand smoke. This exposure risks causing fetal growth disorders, low birth weight, and respiratory infections in toddlers. This community service activity aims to increase fathers' knowledge about the dangers of smoking through health counseling. The method used was interactive lecture with leaflet media and suction bottle props. The targets of the activity were 25 fathers in RW 6 Sembungharjo Village, Semarang City. The evaluation results showed an increase in respondents' knowledge, from 72% with good knowledge before the intervention to 88% after the intervention. This health education is effective as a promotive and preventive measure to reduce the risk of exposure to cigarette smoke in the family environment, thus creating a healthier household for mothers and children.